(untitled) (Itinera, 2022)
The article aims to shed light on the peculiar relationship between Blossfeldt’s photographic aesthetics and that of Moholy-Nagy in a novel way. I intended to show, starting with the essay “Short History of Photography” and the review “News about flowers” by Walter Benjamin, the peculiar character of Blossfeldt’s photographs collected in his book Urformen der Kunst (1928). What emerges from this photo-collection is first and foremost a fundamental ontological difference between photo-graphs and pictorial chrome-graphs, which I have developed through comparison with Gadamer’s reflection on the portrait. I then showed the profound affinity of Blossfeldt’s photography with Riegl’s reflection on ornamentation, Goethean morphology and Klee’s painting. Despite the apparent proximity of Blossfeldt’s work to traditional photography and the so-called Neue Sachlichkeit, I have argued, in the last part of the contribution, the affinity of this work to certain aspects of Moholy-Nagy’s Neue Sehen. Like Moholy-Nagy, Blossfeldt intends to implement the perceptual possibilities of the human being, giving him access to a new “optical unconscious”.